A critical review of prevention, treatment, reuse, and resource recovery from acid mine drainage. (20th December 2021) - Chen, Guan; Ye, Yicheng; Yao, Nan; Hu, Nanyan; Zhang, Jie; Huang, Yang
Abstract: Acid mine drainage (AMD) causes serious environmental pollution owing to its high acidity, toxic metal content, and sulfate content. This review describes the mechanism of formation and the effects of AMD, presents the prevention and treatment technologies, identifies critical research gaps, and explores the challenges and opportunities encountered by AMD prevention and treatment technologies. Although passivation and microencapsulation technology have good prospects, they are in the early experimental stage and focus on pure pyrite systems. Remediation technologies such as chemical neutralization, adsorption, microbial activity, and membrane technologies have been developed to reduce the negative impacts of AMD on environment and human health; however, a continuous supply of chemicals and energy, expensive maintenance costs, and long-term monitoring of the affected ecosystem are some of its limitations. The recovery and reuse of valuable resources (sulfuric acid, metals, and rare earth elements) during AMD treatment can reduce its cost and is crucial in achieving a sustainable treatment. Membrane technology can produce high-quality water, but cannot achieve resource recovery, especially selective recovery of valuable metals. The integrated of membrane and other technologies can realize the reuse of water and the recovery of valuable resources. In addition, the recycling of mine tailings as construction materials and geopolymers can greatly reduce the formation of AMD. Overall, this review provides resource recovery and reuse as a holistic approach to sustainable AMD treatment. Finally, integrated treatment technologies that is worthy of future exploration need to be emphasized. Graphical abstract: Image 1 Highlights: Acid mine drainage presents dire environmental impact. Carrier microencapsulation process is the most promising prevention technology. Remediation options are effective, but unsustainable. Water reuse and valuable resource recovery potentially offset AMD treatment costs. Integrated processes are prospective approaches for AMD treatment.